DELINEASI AREA PROSPEK DAN KARAKTERISASI RESERVOIR PANAS BUMI NON-VULKANIK UNTUK PEMANFAATAN LANGSUNG DI BANDA BARU, MALUKU TENGAH: PROSPECT AREA DELINEATION AND CHARACTERIZATION OF NON-VOLCANIC GEOTHERMAL RESERVOIRS FOR DIRECT USE IN BANDA BARU, CENTRAL MALUKU - Melisano, Erawan; Nugraha, Husin Setia; Rahadinata, Tonny; Sumintadireja, Prihadi (Buletin Sumber Daya Geologi, 2025)
The significant disparity between Indonesia's geothermal direct-use potential (230 MWt) and its current utilization (8 MWt) necessitates precise delineation methods for non-volcanic systems. This study aims to characterize the shallow reservoir and delineate the prospect area in Banda Baru, Central Maluku, using integrated geoscience data. A GIS-based Multi-Influencing Factor (MIF) method was applied to map groundwater potential, which was then synthesized with surface CO2 gas anomalies and Magnetotelluric (MT) resistivity gradient modeling. The results identified a 6.49 km2 prospect area controlled by fracture structures within metamorphic rocks. Validation through the BBR-1 temperature gradient well drilling showed significant success, encountering 95°C fluid at a depth of 164 meters. This finding prompted a re-evaluation of geophysical interpretations, proving that low resistivity values (<50 ohm-m) represent active thermal aquifers rather than conventional clay caps. Based on production tests, the total measured resource potential in this region is estimated at 6.3 MWt. This integrated modeling provides a strategic instrument for efficient non-volcanic geothermal development to support the local economy through sustainable direct-use schemes.